Diffuse Alveolar Haemorrhage in Childhood Systemic Lupus Erythematous With Good Response to Oral Steroid Therapy - Kini, Pushpa Gurudas; Moras, Karen; Kumar, Sandeep; Shetty, Deepti (Journal of Nepal Paediatric Society, 2019)
Diffuse alveolar hemorrhage (DAH) is a relatively rare and life threatening complication of systemic lupus erythematosus (SLE) in childhood. We report two distinct cases of SLE presenting with DAH as the sole manifestation of the disease during long term follow up. Both were successfully treated with oral prednisolone.